Transition of Civil Law to Public Law: Integration of Modern Punishment Theory in Criminal Apostasy - Dedy Sumardi; Mukhsin Nyak Umar; Ruslan Sangaji; Firdaus M Yunus; Rahmatul Akbar (Universitas Islam Negeri Jakarta, 2022)
This paper aims to analyze the determination of death penalty in apostasy through modern criminal theories and human rights considerations. The approach is used to objectively view the purpose of death penalty on a criminal act in the context of religious freedom. This study is a conceptual study using the library research and descriptive-analytical approach. Based on the analysis of punishment theories, it is found that the determination of the death penalty in apostasy takes a combined pattern of punishment theories: retributive, deterrence, and reformative theories. The combination of these theories leads to an integration, as it does not focus only on the retributive and deterrence aspects, but it also emphasizes on the reformative aspect, as a means of therapy for apostate criminals so they will not repeat the same acts. The integration of the theories seems perfect when accompanied by moral education that can provide “spiritual enlightenment”, so that criminals can be accepted back into the community. The integrity-morality theory or pulse-integrity theory is expected to neutralize the difference in views on the purpose of punishment in Islamic criminal law, which has long been considered not in line with the norms of human rights under the pretext of the sovereign system of the nation-state, where citizenship status is limited by territorial areas. The equality of rights, justice, morality, and individual accountability is a universal principle of the teachings of the Qur’an which inspire the conception of human rights norms by every citizen.AbstrakArtikel ini menganalisis penetapan hukuman mati dalam pidana murtad menggunakan pendekatan teori pemidanaan dan pertimbangan hak asasi manusia. Pendekatan ini digunakan untuk melihat secara objektif tujuan ditetapkan hukuman mati sebagai perbuatan pidana dalam konteks kebebasan beragama. Studi ini merupakan kajian konseptual, dianalisis menggunakan data kepustakaan melalui pendekatan deskriptif-analitis. Berdasarkan analisis teori pemidanan ditemukan bahwa penetapan hukuman mati dalam pidana murtad mengambil pola perpaduan teori pemidanaan; teori retributif,deterrence dan reformatif. Perpaduan ketiga teori melahirkan integritas, tidak terfokus pada aspek retributif dan deterrence, tetapi lebih menekankan pada aspek reformatif, sebagai terapi pelaku kajahatan murtad agar tidak mengulangi perbuatan yang sama. Pengintegrasian ketiga teori ini terlihat sempurna manakala diiringi pendidikan moral yang dapat memberikan “pencerahan spiritual”, sehingga pelaku kejahatan dapat diterima kembali dalam kehidupan masyarakat. Teori integritas-moralitas atau teori integritas-plus diharapkan dapat menetralisir perbedaan pandangan tujuan pemidanaan Islam. Persamaan hak, keadilan, moralitas dan pertanggunjawaban individu merupakan prinsip universal ajaran al-Qur’an menjadi inspirasi lahirnya norma hak asasi manusia setiap warga negara.